Menurunkan Intensitas Burnout Belajar Melalui Dinamika Kelompok di SMP Al-Hikmah Jambuan Boarding School - Arifin Nur Budiono (FKIP Universitas Islam Jember, 2017)
Burnout learning can prevent a person from becoming a personal success desired for his future life. Researchers conducted observations at the junior high school Al-Hikmah Jambuan boarding school class VII even semester of the academic year 2016-2017 and obtained data about 56% or more than half the students who experienced burnout learning. This study aims to reduce the intensity of learning burnout through group dynamics. The type of research used is action research guidance and counseling (PTBK). The procedure used is the cycle model. Based on the results of the research, the first cycle of the first meeting of respondents still shows the attitude of learning burnout. It is shown from student activeness, student interest, student enthusiasm, and conducive student only ranged between 60-66%. The second meeting, respondents have shown a better situation that is about 78%. The first cycle of the first meeting is about 80%. The second meeting, student activity, student interest, student enthusiasm, and conducive students increased, ranging from 89-91%. Thus, it can be concluded that group dynamics can decrease the intensity of learning burnout.Keywords: Learning Burnout, Group Dynamics